2013
DOI: 10.1088/0957-0233/24/6/065003
|View full text |Cite
|
Sign up to set email alerts
|

Applications of profile filtering in the dimensional metrology of fuel cell plates

Abstract: We describe the application of several surface profile filters as an enabling tool in the dimensional measurements of an engineering artifact, namely, a fuel cell plate. We recently reported work on the development of a non-contact system for dimensional metrology of bipolar fuel cell plates. That system is comprised of two laser spot triangulation probes that acquire profile data across a plate. While the non-contact system provides rapid measurements (measurement speed of 100 mm/s to 500 mm/s), the data are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…It has been stated that CMM mounted laser scanners are at least one order of magnitude less accurate than touch trigger probe [6]. Although, more recent studies have found an improvement is laser scanner accuracy [3,5], which this study has also found. Considering measurements against a known diameter, the touch trigger probe measurement results deviated by at worst 16.7 μm compared to 27.1 μm when the sphere diameter was measured with the laser scanner.…”
Section: Effect Of Surface Point Locationsupporting
confidence: 43%
See 2 more Smart Citations
“…It has been stated that CMM mounted laser scanners are at least one order of magnitude less accurate than touch trigger probe [6]. Although, more recent studies have found an improvement is laser scanner accuracy [3,5], which this study has also found. Considering measurements against a known diameter, the touch trigger probe measurement results deviated by at worst 16.7 μm compared to 27.1 μm when the sphere diameter was measured with the laser scanner.…”
Section: Effect Of Surface Point Locationsupporting
confidence: 43%
“…To do this, the vector crossproduct was calculated using the x-axis vector and a vector formed by the line between the two rear datum plates, (2). The vector cross-product between the xand z-axes was then used to form the y-axis, (3). The x-, yand z-axes unit vectors were then combined to form the transformation matrix R, (4).…”
Section: Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation